2013
DOI: 10.1007/s13142-013-0208-1
|View full text |Cite
|
Sign up to set email alerts
|

User-centered development of a smart phone mobile application delivering personalized real-time advice on sun protection

Abstract: Smart phones are changing health communication for Americans. User-centered production of a mobile application for sun protection is reported. Focus groups (n=16 adults) provided input on the mobile application concept. Four rounds of usability testing were conducted with 22 adults to develop the interface. An iterative programming procedure moved from a specification document to the final mobile application, named Solar Cell. Adults desired a variety of sun protection advice, identified few barriers to use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 57 publications
3
57
0
1
Order By: Relevance
“…Users were particularly interested in the Sun alert service, highlighting the value of receiving prompts and advice in convenient place (eg, holiday setting). These findings, although preliminary, are very promising and align with those found in other investigations of mobile apps to promote sun protection, in which usage and acceptability have been similarly demonstrated [11,12,35]. The systematic and iterative development of the app [15] and the theory-driven nature of the app [42], including active components shown to be key in interventions promoting sun protection [13], may have led to greater usage.…”
Section: Comparison With Other Studiessupporting
confidence: 82%
See 1 more Smart Citation
“…Users were particularly interested in the Sun alert service, highlighting the value of receiving prompts and advice in convenient place (eg, holiday setting). These findings, although preliminary, are very promising and align with those found in other investigations of mobile apps to promote sun protection, in which usage and acceptability have been similarly demonstrated [11,12,35]. The systematic and iterative development of the app [15] and the theory-driven nature of the app [42], including active components shown to be key in interventions promoting sun protection [13], may have led to greater usage.…”
Section: Comparison With Other Studiessupporting
confidence: 82%
“…The need for more intelligent and interactive systems has been reported previously [34]. The study by Buller and colleagues [35] also shows that participants were interested in a system that would (1) display how long they could be exposed to the sun without burning (including vitamin D synthesis), (2) show daily UV levels, (3) advice on recommended SPF, and (4) send prompts to reapply sunscreen. Nevertheless, such a system would need to tackle some of the uncertainties related to vitamin D synthesis and sunscreen use.…”
Section: Principal Findingsmentioning
confidence: 89%
“…Another critical consideration is how to use interface designs to best engage the target population. In this special issue, Buller and colleagues [19] provide an excellent guide for academics on the formative user-centered development process they employed to create a smart phone mobile application for sun protection. They obtained feedback from end users throughout development to ensure that the final product met user needs, was easy to use, and designed in a way that ensures users trust the product's advice.…”
Section: Who Should Be Involved In the Developmental Process Of Emergmentioning
confidence: 99%
“…Buller et al have published their work [18,19,20] reporting on the development of the app Solar Cell, designed for the Android smartphone, and where the aim is to provide real time sun protection advice. The pilot stage included the running of focus groups for conceptual determination [18], followed by four rounds of usability testing to develop the app interface.…”
Section: Discussionmentioning
confidence: 99%
“…Further research [19] included a randomised controlled trial pre-test post-test design with 10 week follow up for usability testing and to assess if the system was interoperable across handsets and networks. The system was found to be highly user friendly with a mean of 5.06 (Range 0 = worst imaginable to 7 = best imaginable) [20]. With regards to Vitamin D related outcomes, the research for the Solar cell app found that it helped with some improved sun protection.…”
Section: Discussionmentioning
confidence: 99%